PENGARUH E-COMMERCE TERHADAP MINAT PEREMPUAN BERWIRAUSAHA BISNIS ONLINE DITENGAH PANDEMI COVID-19 KOTA PEKANBARU - Sufnirayanti Sufnirayanti; Jahrizaldan Jahrizaldan; Any Widayatsari (PEKBIS, 2021)
The main purpose of this research is to analyze the effect of E-commerce on the interest of women in online business entrepreneurship amid the Covid-19 pandemic in Pekanbaru City. The location of the research was done purposively, namely in Pekanbaru City, Riau Province. Data analysis in this study used quantitative descriptive methods. The population in this study were all MSME Entrepreneurs in 2019, namely 4,112 people. In determining the sample size, the formula: Slovin and obtained 98 respondents. Based on the research that has been done, the results of simple regression analysis with the results are Y = 20,433 + 1,062 X, the value of a is 20,433, this value shows that when the E-commerce variable (variable X) is zero, then the interest in entrepreneurship through online business ( variable Y) of 20,433. While the value of b is 1.062, meaning that when there is an increase in the value of the e-commerce variable (variable X) by 1 (one) unit, the interest in entrepreneurship (variable Y) will increase by 1.062 units. The coefficient of determination (R Square) is 0.698 or 69.8%. So it can be concluded that the e-commerce variable contributed to changes in women's interest in entrepreneurship through online businesses during the Covid-19 pandemic by 69.8%. while the remaining 30.2% (100% -69.8%) was influenced by other factors not examined in this study. The t-count value was 14.904. While the critical value according to the table with a significance level of 5% using the t table formula (α / 2; n - k) k = 2 and n = 98 - 2 = 96 is 1.98498, because tcount> t table, Ho is rejected. This means that there is an influence by the E-commerce variable on the customer satisfaction variable. With the meaning of the word Hypothesis (Ha) is accepted.